From liberal paralysis to green republican resolution? Conceptualising, illustrating, and addressing problems of governability in eco-social politics - Selk, Veith; Klüh, Niklas (Frontiers in Political Science, 2025)
The phenomenon of ungovernability is by no means new and had already been described 50 years ago in the literature, but awareness of its importance has only recently been reawakened. From that starting point, this article develops a conceptual scheme of the problems governments are currently facing in their efforts to address eco-social issues, namely politicisation overload, political inequality, the “freedom-first trap”, and a structural legitimacy deficit. The heuristic potential of this scheme is then illustrated by way of the debates on the Buildings Energy Act in Germany. Given the inability of liberalism as a political paradigm to solve these problems, this article offers initial suggestions as to whether republicanism, as an alternative paradigm for environmental politics, can respond to the structural challenges of governing.